MODE OF PRESENTATION AND MANAGEMENT OF CAROTID ARTERY INJURIES - Nauman Imtiaz (Army Medical College Rawalpindi, 2018)
Objective: To share experience of presentation and management of carotid artery injuries in tertiary care Hospitals Rawalpindi, Lahore and Quetta. Study Design: Cross sectional descriptive study. Place and Duration of Study: Combined Military Hospital Rawalpindi Lahore and Quetta, from Jun 2005 to Jul 2014. Material and Methods: The data of demography, mode of presentation, associated injuries and surgical procedures performed in the patients with penetrating neck injuries were collected and analyzed descriptively. Results: All 32 patients were male. Age ranged from 18 to 52 years (mean: 30.7 ± 7.1 years). Time of presentation to vascular surgeon ranged from 1 to 52 hours (mean: 4.4 ± 2.3 hours). Sixteen cases (50%) resulted from shrapnel injuries. Thirteen patients (40.6%) had bullet injuries and in three (9.3%), stab wounds. In only 6 cases (18.7%) carotid injury was confirmed on angiography preoperatively. Common carotid artery (CCA) was the most frequently injured artery in 15 cases (46.8%). There were 6 cases (18.7%) of External carotid artery (ECA), 4 (12.5%) cases of internal carotid artery (ICA) and 1 case (3.1%) of injury to the carotid bifurcation. Two cases (6.2%) had both ICA and ECA injuries. Four patients (12.5%) had no carotid artery injury on surgical exploration. Conclusion: Surgical exploration of neck penetrating injuries on the basis of hard signs and platysmal penetration was found a safe procedure especially in patients who had history of hemodynamic instability.